Implementation of the Pancasila Student Profile Strengthening Project (P5) in Elementary Schools - Nurmala, Viviani; Astiti, Niken Yuni; Fitri, Dina Martha; Wuryandani, Wuri (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study investigates the existing gap in research concerning the implementation of the Project for Strengthening the Pancasila Student Profile (P5) in elementary schools. The primary goal is to analyze how P5 is executed and assess its effectiveness in promoting character development among students. Additionally, the research aims to identify the factors that support and the challenges faced in implementing P5 within educational settings. This qualitative research included seven subjects: a school principal, a curriculum officer, two project teachers, two students, and one guardian. The study utilizes Robert K. Yin's case study methodology and focuses on a single-case approach. Data were gathered through interviews, observations, and documentation. The analysis employed Miles and Huberman's interactive model, encompassing data reduction, display, and conclusion drawing. The results indicate that implementing P5 significantly contributes to students' ability to incorporate the Pancasila Student Profile into their daily lives. The active involvement of teachers, students, parents, and the broader community is critical to achieving this goal. The identified characteristics associated with P5 include faith, dedication to God, moral integrity, teamwork, global inclusivity, and innovation. The successful implementation of P5 is contingent upon the proactive engagement of teachers, support from parents, availability of adequate facilities, and effective leadership from the principal. However, the study also identifies several challenges, including time constraints, diverse student characteristics, the integration of technology, and occasional resistance from parents. By addressing these challenges, educational institutions can enhance the implementation of P5, thereby facilitating the internalization of Pancasila values in students' educational experiences and daily interactions.